Effect of the bound nucleon form factors on charged-current neutrino-nucleus scattering - Tsushima, K. [UNESP]; Kim, Hungchong; Saito, K. (American Physical Society (APS), 2004)
We study the effect of bound nucleon form factors on charged-current neutrino-nucleus scattering. The hound nucleon form factors of the vector and axial-vector currents are calculated in the quark-meson coupling model. We compute the inclusive 12C(νμ,μ-)X cross sections using a relativistic Fermi gas model with the calculated hound nucleon form factors. The effect of the bound nucleon form factors for this reaction is a reduction of ∼8% for the total cross section, relative to that calculated with the free nucleon form factors.